Students’ test anxiety and its correlation with their academic performance - Fitria, Nur Ainani (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2013)
This study aimed to identify the levels of test anxiety experienced by EFL students, the factors contributing to their test anxiety, and the correlation between test anxiety and academic performance. The study employed a descriptive analytical method using an ex post facto research design. The findings revealed that students experienced varying levels of test anxiety, namely low, moderate, and high; however, overall, the students demonstrated a very low level of anxiety. Factors influencing test anxiety related to test-taker characteristics included self-image, perceptions of others, preparation, future security, testing situations, motivation to achieve high scores, personal problems, and situational as well as subjective determinants. Meanwhile, factors related to test characteristics included item difficulty sequencing, item types, test-taking information, test length, and time pressure. Finally, the results indicated that students’ test anxiety had no significant correlation with their academic performance.